Brown gold : milestones of African-American children's picture books, 1845-2002 - Martin, Michelle H., 1966- (Routledge, 2004)
Brown Gold is a compelling history and analysis of African-American children's picturebooks from the mid-nineteenth century to the present. At the turn of the nineteenth century, good children's books about black life were hard to find -- if, indeed, young black readers and their parents could even gain entry into the bookstores and libraries. But today, in the "Golden Age" of African-American children's picturebooks, one can find a wealth of titles ranging from Happy to be Nappy to Black is Brown is Tan. In this book, Michelle Martin explores how the genre has evolved from problematic early works such as Epaminondas that were rooted in minstrelsy and stereotype, through the civil rights movement, and onward to contemporary celebrations of blackness. She demonstrates the cultural importance of contemporary favorites through keen historical analysis -- scrutinizing the longevity and proliferation of the Coontown series and Ten Little Niggers books, for example -- that makes clear how few picturebooks existed in which black children could see themselves and their people positively represented even up until the 1960s. Martin also explores how children's authors and illustrators have addressed major issues in black life and history including racism, the civil rights movement, black feminism, major historical figures, religion, and slavery. Brown Gold adds new depth to the reader's understanding of African-American literature and culture, and illuminates how the round, dynamic characters in these children's novels, novellas, and picturebooks can put a face on the past, a face with which many contemporary readers can identify
Keywords: American literature -- African American authors -- History and criticism.; American literature -- African American authors -- Bibliography.; Children's literature, American -- History and criticism.; Children's literature, American -- Bibliography.; Picture books for children -- United States -- Bibliography.; Picture books for children -- United States.; African Americans in literature.; African Americans in art.; Littérature de jeunesse américaine -- Histoire et critique.; Littérature de jeunesse américaine -- Bibliographie.; Livres d'images pour enfants -- États-Unis -- Bibliographie.; Livres d'images pour enfants -- États-Unis.; Noirs américains dans la littérature.; Noirs américains dans l'art.; LITERARY CRITICISM -- American -- General.; African Americans in art; African Americans in literature; American literature -- African American authors; Children's literature, American; Picture books for children; United States; Bibliographies; Criticism, interpretation, etc.